Cracking mechanism in API 5L X65 steel in a CO2-saturated environment – Part II: A study under cathodic polarisation. (July 2020) - Silva, S.C.; Silva, A.B.; Folena, M.C.; Barker, R.; Neville, A.; Ponciano Gomes, J.A.C.
Highlights: Hydrogen embrittlement occurs in X65 steel cathodically polarised in CO2 environment. The embrittlement effects depend on the steel surface composition. Pre-corroded Fe3 C enriched surface increases hydrogen permeation. FeCO3  film promotes high hydrogen permeation at outset which decreases over time. Abstract: The aim of this work is to achieve a better understanding of hydrogen effect in CO2 environments, isolating its contribution by imposing cathodic polarisation on Hydrogen Permeation (HP) and Slow Strain Rate Tests (SSRTs). The influence of Fe3 C and FeCO3 layers on hydrogen embrittlement (HE) susceptibility was a specific focus of this study. The results indicate that CO2 environment generates hydrogen, which permeates through steel, although in lower amount compared to H2 S environments. Moreover, in Fe3 C-rich surface, the HP current achieves values higher than in wet-ground surface. Furthermore, in FeCO3 -filmed surface HP current is higher at the beginning of the test but decreases over time. The results of SSRT show the loss of ductility of the steel under cathodic polarisation that was driven by hydrogen and the embrittlement effect magnitude depends on the surface condition, indicating that a pre-corroded steel surface can raise the HE susceptibility in a CO2 environment.